Rapid photothermal heating of aqueous batteries for low-temperature conditions - Zhichun Yu; Jiaxing Liang; Jian Pan; Jiangtao Xu; Guojin Liang; Zhifang Shi; Wei Feng; Dewei Chu; Ruopian Fang; Da-Wei Wang (Energy Materials and Devices)
Aqueous batteries are promising for large-scale applications owing to their affordability, eco-friendliness, and nonflammability. However, their usability in cold regions is limited by electrolyte freezing and slow ion-transfer kinetics at subzero temperatures. This study demonstrates the stable operation of aqueous batteries in subzero conditions by integrating high-efficiency photothermal current collectors with suspension electrodes. The Ketjen black-based photothermal current collectors efficiently convert a broad spectrum of sunlight (98%, 200–2500 nm) into thermal energy, enabling rapid heat generation. Simultaneously, the high thermal conductivity of the suspension electrode ensures quick distribution of thermal energy throughout the battery. This configuration allows the cell’s core temperature to rapidly increase from −18 °C to 20 °C within 22 min under simulated solar irradiation. Additionally, an integrated light concentrator and temperature regulation system has been developed to improve heating rates and ensure the temperature stability of the cell under various climatic conditions. As a result, the cell can maintain a stable temperature of 20 °C during consecutive charge/discharge cycles, even with an ambient temperature fluctuating between −5 °C and 5 °C. This integrated photothermal battery design exhibits great potential for cold weather conditions, paving the way for the deployment of large-scale aqueous battery systems in polar regions.